Rethinking the Neighbourhood Parks of Dhaka city through the Spectacle of Universal Design to Ensure Accessibility for the Differently Abled People - Suchana, Sarah Bashneen; Khan, Muzaiana Naomi; Shoilee, Sumaiya Murshida (Journal of Bangladesh Institute of Planners, 2020)
The demand of neighbourhood parks with provision of universal accessibility is an inevitable prerequisite for enhancing quality of life of all people, regardless of their age, size, disability or ability. Lack of universal accessibility neighbourhood parks creates impact on frequency of uses of differently able people. This paper therefore first study the definition and of universal design and accessibility as well as standard guidelines of different countries, and secondly find out the plug-ins that are necessary for creating an environment which can be recognized as universally accessible. A comparative study of standards and guidelines of different countries for universal access to the external environment with BNBC is carried out and an observational field survey has been done, evaluating the six neighbourhood parks of Dhaka city as case studies. Based on the findings, this paper represents a rational layout emphasizing on the universal accessibility to increase the interaction and comfort of differently abled people in the neighbourhood parks of Dhaka. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 69-88